THE IMPLEMENTATION OF PODCAST TO DEVELOP STUDENTS’ LISTENING SKILL AT THE ELEVENTH GRADE OF MAN KOTA PALANGKA RAYA - Ikrimah; Karani, Elanneri (English Education Department of STKIP Pasundan, 2023)
This study's goal is to find out the different result of the students who taught using podcast and conventional in teaching listening. Listening is when someone pays attention to what a speaker is saying and tries to understand and make sense of what the speaker is saying. Since there are still many students think that listening is very hard to them, so the teacher should also be focused on how to create an environment that is conducive, fun, exciting, and fascinating to learn in order to improve learning outcomes for their students. One attempt is to incorporate media into the educational process, the media that could be used in teaching listening is by using podcast. A podcast is an online audio file that may be downloaded onto a personal computer or mobile device. Podcasts are often presented as part of a series, and listeners can sign up to get new episodes of the series automatically when they are released. The researcher used a quantitative method for this work. The study was quasi-experimental: Pre- and post-test, non-randomized control group. The samples are the students from XI IPS 1 dan XI IPS 2, which consist of 70 students. In this study, the research tool was used a test. The test here was multiple choice with 15 items of question. Based on the findings, the alternative hypothesis (Ha) which said there is a difference results between classes taught using podcast and classes taught using conventional to develop students’ listening skill at the eleventh grade of MAN Kota Palangka Raya was accepted. The null hypothesis (H0), which stated that there is no difference results between classes taught using podcast and classes taught using conventional to develop students’ listening skill at the eleventh grade of MAN Kota Palangka Raya was rejected. It indicates that the implementation of podcast as a media is more effective in listening activities than conventional style of teaching.